2013
DOI: 10.1136/bmjopen-2013-003293
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in recently arrived immigrants from Africa and Asia: a cross-sectional study from Norway of children, adolescents and adults

Abstract: ObjectivesTo estimate the prevalence of vitamin D deficiency (25(OH)D) <50 nmol/L among recently arrived immigrants from Africa and Asia in Oslo, and to explore 25(OH)D levels according to origin, gender and age.DesignA cross-sectional study.SettingPrimary healthcare unit in Oslo, Norway, offering family immigrants, asylum seekers, United Nations (UN) refugees or individuals granted asylum a free medical examination on arrival.ParticipantsAll individuals from African and Asian countries (n=591) referred to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 32 publications
5
50
1
6
Order By: Relevance
“…There are no data on vitamin D status in Somali women living in Somalia. A Norwegian study on recently arrived immigrants from Africa showed that 73% had S‐25(OH)D < 50 nmol/l and 24% had S‐25(OH)D < 25 nmol/l …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no data on vitamin D status in Somali women living in Somalia. A Norwegian study on recently arrived immigrants from Africa showed that 73% had S‐25(OH)D < 50 nmol/l and 24% had S‐25(OH)D < 25 nmol/l …”
Section: Discussionmentioning
confidence: 99%
“…This is a long time, relative to the~2-week half-life of S-25(OH)D. 19 There are no data on vitamin D status in Somali women living in Somalia. A Norwegian study on recently arrived immigrants from Africa showed that 73% had S-25(OH)D < 50 nmol/l and 24% had S-25(OH)D < 25 nmol/ l. 20 Clothing habits may affect vitamin D status in young immigrant women. 21 All subjects in the present studies were veiled.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is prevalent worldwide and high prevalence of vitamin D insufficiency and secondary hyperparathyroidism (SHPT) among non-Western immigrant populations living in Western countries has been reported (Islam et al, 2012, Meyer et al, 2004, Lowe et al, 2010). Recent studies in Norway have shown that in immigrants with background from Sub-Sahara Africa, Middle East and South Asia, nearly 80% had 25(OH)D < 50 nmol/L and approximately one-third had 25(OH)D < 25 nmol/L regardless of season (Eggemoen et al, 2013, Madar et al, 2009, Holvik et al, 2005). These studies suggest that the impact of vitamin D deficiency on the skeletal homeostasis of immigrants is of concern (Roy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, a study has been performed in 2013 to compare the serum vitamin D levels among different populations living in Norway. The results of this study have revealed that immigrants from South Asia, the Middle East, and Africa were found to be more vitamin D-deficient (25-(OH) D < 20 ng/mL) than East Asians (63). Notably, the authors have recommended the routine measurement of vitamin D levels and early detection of vitamin D deficiency in these populations (Middle East and Africa).…”
Section: Discussionmentioning
confidence: 74%